Boron-rich layer removal and surface passivation of boron-doped p–n silicon solar cells *Project supported by the Beijing Municipal Science and Technology Commission, China (No. Z151100003515003), the Beijing Natural Science Foundation (No. 4173077, 2184112), the Fundamental Research Funds for the Central Universities, China (Nos. FRF-BR-16-018A, FRF-TP-17-022A1, 06400071), the National Natural Science Foundation of China (Nos. 110751402347, 61274134, 51402064, 61274059, 51602340), the Beijing Municipal Innovation and Research Base, China (No. Z161100005016095), and the Youth Innovation Promotion Association of Chinese Academy of Sciences (No. 2015387). (December 2018) - Hou, Caixia; Jia, Rui; Tao, Ke; Jiang, Shuai; Zhang, Pengfei; Sun, Hengchao; Liu, Sanjie; Peng, Mingzeng; Zheng, Xinhe
Abstract: In boron-doped p + –n crystalline silicon (Si) solar cells, p-type boron doping control and surface passivation play a vital role in the realization of high-efficiency and low cost pursuit. In this study, boron-doped p + -emitters are formed by boron diffusion in an open-tube furnace using borontribromide (BBr3 ) as precursor. The formed emitters are characterized in detail in terms of shape of the doping profile, surface doping concentration, junction depth, sheet resistance and removal of the boron-rich layer (BRL). In the aspect of BRL removal, three different methods were adopted to investigate their influence on device performance. The results demonstrate that our proposed chemical etch treatment (CET) with the proper etching time could be an effective way to remove the BRL. After removal of the BRL, Al2 O3 /SiN x stacks are deposited by atomic layer deposition (ALD) and plasma-enhanced chemical vapor deposition (PECVD) to passivate the cell surface. It was found that a reasonably-high implied V oc of 680 mV has been achieved for the fabricated n-type Si solar cells.